Hybrid Polymer Composite Materials : Processing - Thakur, Vijay Kumar, 1981-; Thakur, Manju Kumari; Gupta, Raju Kumar, 1982- (Woodhead Publishing, 2017)
This book presents the latest on these composite materials that can best be described as materials that are comprised of synthetic polymers and biological/inorganic/organic derived constituents.
Keywords: polymery; polymerní kompozitní materiály; polymers; polymer composite materials; kolektivní monografie; elektronické knihy; collective monographs; electronic books